(untitled) (Journal of Applied Learning and Teaching, 2025)
Computer operating systems are often an overlooked part in providing quality education. When discussing digital education tools, most practitioners and researchers mainly focus on hardware (e.g. PC, notebook, tablet, and smartphone) and software applications that directly interact with students. While Microsoft Windows is widely recognized, other alternatives remain relatively unknown. This paper introduces an alternative approach by examining the potential of open-source operating systems such as Linux, particularly focusing on Edubuntu, a flavour of Ubuntu operating system, designed specifically for education. It also explores available default applications and investigates how Edubuntu can provide expansive learning opportunities that develop learners’ interest and help cultivate 21st century skills. Importantly, we pose the question of how to harness the potential of Edubuntu potential effectively. We then illuminate Edubuntu’s capacity to support traditional subjects as well as promote computational thinking and geographic education. Lastly, we analyze Edubuntu with respect to instructional software design standards and summarize key consideration factors in designing an educational operating system.